Ultra-high temperature bacterial agents enhance heavy metal passivation and antibiotic degradation in compost - Chi, Zifang; Zhang, Shengyi; Li, Yuru; Li, Huai (Frontiers in Microbiology, 2025)
The co-contamination of heavy metals and antibiotics in livestock manure presents a significant environmental challenge. This study developed an integrated ultra-high-temperature (UHT) composting process to address this issue. Through an L9(34) orthogonal experiment, we optimized key parameters and identified 60% moisture content, 25:1 carbon-to-nitrogen (C/N) ratio, and 10% (w/w) activated carbon addition as the optimal combination, with activated carbon being the most influential factor. In pilot-scale validation, bioaugmentation with a specialized UHT microbial consortium (UHTMC) at 1.0% dosage achieved a peak temperature of 84.3 °C, maintaining temperatures above 70 °C for 15 days and above 50 °C for 28 days, which significantly surpassed the control. This enhanced thermophilic profile drove superior co-removal performance: 56.0% copper (Cu) and 57.3% zinc (Zn) passivation rates, representing improvements of 11.3 and 11.1 percentage points over the control, respectively, and near-complete degradation (> 99.4%) of tetracycline (TC), oxytetracycline (OTC), and chlortetracycline (CTC). This work demonstrates that bioaugmented UHT composting synergistically enhances microbial activity, effectively passivates heavy metals, and completely degrades antibiotics, providing an efficient resource-oriented strategy for treating co-contaminated solid waste.